Amlodipine/valsartan fixed-dose combination treatment in the management of hypertension: A double-blind, randomized trial. Issue 10 (17th July 2020) - Wang, Kang-Ling; Yu, Wen-Chung; Lu, Tse-Min; Chen, Lung-Ching; Leu, Hsin-Bang; Chiang, Chern-En
Abstract : Background: To compare the fixed-dose combination (FDC) of amlodipine/valsartan 5/80 mg with valsartan 160 mg monotherapy for efficacy and safety in hypertensive patients. Methods: We designed this double-blind, randomized, and noninferiority trial in which patients with elevated systolic blood pressure (SBP) and/or diastolic blood pressure (DBP) were randomly assigned to receive amlodipine/valsartan 5/80 mg FDC or valsartan 160 mg monotherapy for 8 weeks. The primary endpoint was changes in office SBP and DBP from baseline to 8 weeks. Twenty-four-hour blood pressure (BP) and the incidence of adverse events were recorded. Results: A total of 42 patients underwent randomization. At 8 weeks, office SBP changes were –16.5 ± 15.5 mmHg ( p < 0.001) with amlodipine/valsartan 5/80 mg FDC and –6.9 ± 11.4 mmHg ( p = 0.012) with valsartan 160 mg monotherapy while corresponding changes in office DBP were –9.8 ± 7.7 mmHg ( p < 0.001) and –2.5 ± 6.6 mmHg ( p = 0.095), respectively. The between-group differences were –9.6 mmHg (95% CI, -18.1 to -1.1; p = 0.028) for SBP and –7.3 mmHg (95% CI, -11.8 to -2.8; p = 0.002) for DBP. Furthermore, reductions in both 24-hour SBP (–9.2 mmHg; 95% CI, -16.4 to -2.1; p = 0.013) and DBP (–4.6 mmHg; 95% CI, -9.2 to -0.1; p = 0.048) were consistently greater with amlodipine/valsartan 5/80 mg FDC than with valsartan 160 mg. Overall, 27 and 23 adverse events occurred in the amlodipine/valsartan 5/80 mg FDC group and in the valsartan 160 mg monotherapy group, respectively. The majority were mild and were not related to study medications. There were no significant differences in safety between two treatments. Conclusion: Efficacy of amlodipine/valsartan 5/80 mg FDC was superior to that of valsartan 160 mg monotherapy while both treatments were well-tolerated.